Is Self-Efficacy Related to Quality of Vascular Access Care in Double Lumen Hemodialysis Patients? - Nurrohim, Muhamad; Indriyawati, Nina; Trisnaningtyas, Wenny; Sudiarto, Sudiarto (JENDELA NURSING JOURNAL, 2025)
Background: Self-efficacy is a crucial factor in the success of therapy and self-care among haemodialysis patients. The quality of vascular access care, particularly in users of double lumen catheters, significantly affects therapy effectiveness and is prone to complications such as thrombosis, which may lead to vascular access loss in 30–40% of patients. Approximately 60% of cases show suboptimal haemodialysis therapy. Studies examining the relationship between self-efficacy and vascular access care quality remain limited in patients using double lumen catheters.Purpose: This study aimed to analyse the relationship between self-efficacy and vascular access care quality in haemodialysis patients with double lumen catheters at Hospital.Methods: A descriptive correlational study with a cross-sectional approach was conducted on 60 purposively selected respondents. The CKD-SE and SF-VAQ questionnaires were used as instruments. Data were analysed using the Spearman Rank test.Results: A significant positive correlation was found between self-efficacy and vascular access care quality (p = 0.000; r = 0.620). Most respondents (68.3%) had moderate self-efficacy (mean 65.49 ± 4.755), and 31.7% had high self-efficacy (mean 85.26 ± 4.121). The quality of vascular access care was moderate in 50% and good in 43.3% of respondents (means 49.40 ± 5.001 and 70.00 ± 5.713, respectively).Conclusion: Patients with high self-efficacy generally provide better vascular access care, supporting the success of haemodialysis. Thus, nursing interventions should aim to enhance self-efficacy to improve care quality in patients with double lumen catheters.